Effects of physical exercise on college students’ sense of meaning in life: the chain mediating role of stress perception and mental toughness - Jiang, Yong; Cao, Yue (Frontiers in Psychology, 2025)
Physical exercise has a significant effect on college students’ sense of meaning in life, and is an important way to promote college students’ mental health and enhance their sense of meaning in life. To explore the relationship between stress perception, mental toughness in college students’ physical exercise and college students’ sense of meaning in life. The scale was used to measure 604 college students and statistically analyzed using SPSS29.0 and Process 4.1. The results showed that the direct positive effect of physical exercise on college students’ sense of meaning in life was significant (effect value = 0.00297, accounting for 62.39% of the total effect). Through the independent mediation path, physical exercise can indirectly affect the sense of meaning of life by decreasing stress perception (negative mediation effect value = −0.00040, accounting for −8.40%) and enhancing mental toughness (positive mediation effect value = 0.00127, accounting for 26.68%). In addition, the chain-mediated path (physical exercise → stress perception → mental toughness → sense of meaning in life) effect of stress perception and mental toughness was significant (effect value = 0.00092, accounting for 19.33%), suggesting that physical exercise first relieves stress perception, then enhances mental toughness, and ultimately enhances the sense of meaning in life. To summarize, physical exercise positively predicts the sense of meaning of life through direct action, and also forms a multiple mechanism of “stress reduction - toughness enhancement - meaning enhancement” through the negative intermediary of stress perception, the positive intermediary of mental toughness, and the chain intermediary effect of the two. Meanwhile, it provides theoretical references for the enhancement of college students’ sense of meaning in life and the improvement of sports health promotion programs.